The Effect of E-Trust, Information Quality and User Interface Quality on E-Customer Loyalty Through E-Satisfaction as an Intervening Variable: (Study on Tokopedia Users in Jabodetabek) - Kedaton, Nyi Raden Sekar; Sadat, Andi Muhammad; Sari, Dewi Agustin Pratama (LPPPIPublishing, 2024)
In this modern era, individuals or groups of people experience high dependence on technology and the digital world. The development of technology and the digital era has changed the way consumers fulfill their needs. Consumers now tend to switch to online purchases, which are considered more practical, fast and efficient than conventional purchases. This study was conducted to determine the effect of e-trust, information quality and user interface quality on e-customer loyalty through e-satisfaction as an intervening variable. The population in this study were Tokopedia users in Jabodetabek. The sample collection technique used was purposive sampling and the sample used was 229 people. The data analysis method used is path analysis with Structural Equation Modeling (SEM), which is then processed using AMOS. The results showed that e-trust has a positive and significant effect on e-satisfaction, information quality has a negative and significant effect on e-satisfaction, user interface quality has a positive and significant effect on e-satisfaction, e-trust has a positive and insignificant effect on customer loyalty, and the variables e-satisfaction, information quality and user interface quality each have a positive and significant effect on customer loyalty, while e-satisfaction is not able to mediate the influence between e-trust, information quality and user interface quality on customer loyalty.